Cobalt-yttrium bimetal oxide / nitride electro-catalytic material as well as preparation method and application thereof
The carbon fiber cloth is modified through dielectric barrier discharge plasma technology and the in-situ synthesized cobalt yttrium bimetallic oxygen/nitride electrocatalytic materials is solved, which solves the shortcomings of carbon-based electrocatalysts in terms of proton transfer efficiency and stability, and achieves efficient and low-cost electrocatalytic performance and long-term stability.
Patent Information
- Application Number
- CN202411947356.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-02-28
AI Technical Summary
Existing carbon-based electrocatalysts perform poorly in terms of proton transfer efficiency and stability, and precious metal catalyst resources are scarce and costly, limiting their application in large-scale industrialization.
The carbon fiber cloth is modified by dielectric barrier discharge plasma technology to increase surface defects, and in situ synthesize cobalt yttrium bimetallic oxygen/nitride electrocatalytic materials in hydrothermal reactions to form electrode materials with high stability and excellent electrocatalytic properties.
The efficient preparation of cobalt yttrium bimetallic oxygen/nitride electrocatalytic materials is achieved, with electrocatalytic properties comparable to traditional precious metal catalysts, and exhibits higher catalytic efficiency and long-term stability at high current density.
Smart Images

Figure CN119530871A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of electrocatalysis technology, and in particular to a cobalt-yttrium bimetallic oxygen / nitride electrocatalytic material and a preparation method and application thereof. Background Art
[0002] The development of clean energy technology has become a hot topic in global research. Among many new energy technologies, water electrolysis technology has become a promising way to obtain clean energy by virtue of its advantages of producing hydrogen and oxygen at the same time. It is widely used in energy storage, fuel cells, chemical production and other fields. Hydrogen energy is considered to be an important part of the future sustainable energy system due to its high energy density and zero carbon emissions. Traditional water electrolysis technology usually relies on precious metal catalysts (such as Pt, Ir, Ru, etc.) to reduce the overpotential of hydrogen evolution reaction (HER) and oxygen evolution reaction (OER), thereby improving the reaction efficiency. However, precious metal resources are scarce and expensive, which limits their application in large-scale industrialization. Therefore, the development of efficient, low-cost and stable non-precious metal catalysts has become a key research direction.
[0003] Compared with traditional powder catalysts, in-situ engineering of catalysts on carbon-based materials has many advantages because: 1) the three-dimensional structure can expose abundant HER and OER active centers; 2) the electrocatalyst is in close contact with the substrate, which reduces the electrochemical impedance, facilitates electron transfer, and increases the electrocatalytic stability at higher current density. Carbon cloth (CC) has good temperature resistance and corrosion resistance, and can remain stable in acidic or alkaline electrolytes, making it an ideal flexible substrate for electrode materials. At the same time, CC can be directly used in hydrogen evolution electrodes due to its large surface area and excellent electrical conductivity.
[0004] However, recent studies have shown that compared with some metal-based catalysts (such as nickel foam or cobalt foam), carbon cloth electrodes perform poorly in proton transfer efficiency and stability, which may be related to the unstable structure formed between the carbon support and the foam. Therefore, the development of cheap, efficient and stable carbon-based electrocatalysts remains a key issue to be solved in the field of electrolysis.
[0005] In order to replace precious metal electrocatalysts with other high-performance catalytic materials, materials such as transition metal oxides, hydroxides, sulfides, and phosphides have been explored. Transition metal oxides (TMOs), especially those containing highly oxidized Co3O4, have recently been considered as favorable alternatives to precious metal oxides for efficient OER in alkaline media. However, their application in the hydrogen evolution reaction HER is not in a dominant state and still needs further improvement. The electrocatalytic activity can be changed by adjusting the electronic structure around the oxide. To overcome the above challenges, the following methods are usually considered:
[0006] (i) Deliberate creation of defects. Defects are induced on the CC surface using DBD plasma technology. Defects can modulate the electronic density of states and surface properties. (ii) Heteroatom doping. Heteroatoms disrupt the periodicity of the catalyst lattice, change the local electronic structure, and introduce additional active sites, thereby enhancing charge transfer. (iii) Multiphase heterostructures. Unlike single-phase materials, the synergistic effect between different phases in multiphase materials can promote the electron transfer rate and help optimize the electronic structure of the material, thereby greatly improving the obtained catalyst activity.
[0007] Yttrium trioxide (Y2O3) is an important rare earth oxide and is widely used in many energy fields. 3 + and Y 4+ The flexible transitions between oxidation states not only endow Y2O3 with reversible surface oxygen ion exchange, acting as an oxygen buffer for efficient oxygen supply, but also provide opportunities for strong electronic interactions with other substrates.
[0008] Therefore, developing a preparation method for cobalt-yttrium bimetallic oxygen / nitride electrocatalytic materials in combination with plasma technology has important research significance and may open up a new research field for advancing clean H2 energy technology. Summary of the invention
[0009] The present invention provides a cobalt-yttrium bimetallic oxygen / nitride electrocatalytic material and a preparation method and application thereof. The electrocatalytic material of the present invention is an electrocatalytic material that uses a carbon fiber cloth (CC) treated by dielectric barrier discharge plasma hydrophilic modification as a substrate and in-situ supports a heterostructure of transition metal cobalt (Co) and rare earth metal yttrium (Y). The preparation process of the present invention is simple and environmentally friendly, and effectively reduces the preparation cost of the electrocatalytic material.
[0010] The present invention firstly utilizes dielectric barrier discharge technology to pretreat the surface of carbon fiber cloth, which can significantly improve the hydrophilicity and surface reaction active area of carbon fiber cloth, enhance the surface reaction activity of carbon fiber cloth, and enhance the binding force between carbon fiber cloth substrate and Y2O3 / YN-Co3O4 cobalt yttrium bimetallic oxide / nitride; then in the hydrothermal reaction process, cobalt yttrium bimetallic oxide / nitride is in-situ synthesized on the carbon fiber cloth substrate to form an electrode material with high stability and excellent electrocatalytic performance.
[0011] The electrocatalytic performance of the electrocatalytic material (catalyst) of the present invention is comparable to that of the traditional noble metal Pt / C catalyst, and exhibits higher catalytic efficiency at high current density. The cobalt-yttrium bimetallic oxygen / nitride catalyst prepared by the method of the present invention not only has excellent electrochemical performance, but also has a gratifying long-term catalytic ability, and has broad market prospects.
[0012] The present invention provides a novel method for preparing high-performance, low-cost transition metal oxide and rare earth metal oxygen / nitride electrocatalytic electrode materials, which has high industrial application prospects and practical application value, especially in the field of energy storage and conversion, and has broad application potential.
[0013] [1] A method for preparing a cobalt-yttrium bimetallic oxygen / nitride electrocatalytic material, comprising:
[0014] Step 1: using dielectric barrier discharge plasma to hydrophilically modify the carbon fiber cloth;
[0015] Step 2: adding the carbon fiber cloth treated in step 1 (referred to as PCC) to a mixed solution containing cobalt (II) nitrate, yttrium (III) nitrate, ammonium fluoride and urea, and placing them together in a high-pressure reactor for hydrothermal reaction to obtain a Y2O3 / YN-Co3O4 cobalt-yttrium bimetallic oxygen / nitride electrocatalyst material;
[0016] The molar ratio of cobalt to yttrium in the mixed solution is 5 to 7:1;
[0017] In the mixed solution, the mass ratio of the total molar number of cobalt and yttrium to the mass ratio of ammonium fluoride and urea is 2mmol:(0.2-0.3)g:(0.4-0.5)g;
[0018] The temperature of the hydrothermal reaction is 230-260°C;
[0019] The hydrothermal reaction time is 8 to 11 hours.
[0020] In the preparation method of the present invention, ammonium fluoride and urea can play the role of complexing agents, and the change in the dosage ratio of ammonium fluoride, urea, cobalt and yttrium will affect the morphology of Y2O3 / YN-Co3O4 cobalt yttrium bimetallic oxygen / nitride. Under the above-defined dosage ratio (the total molar number of cobalt and yttrium and the mass ratio of ammonium fluoride and urea is 2mmol:(0.2-0.3)g:(0.4-0.5)g) and the hydrothermal reaction temperature and time conditions, Y2O3 / YN-Co3O4 cobalt yttrium bimetallic oxygen / nitride has a polyhedral (mainly hexahedral) micro-nano particle structure.
[0021] In step 1, the power of the dielectric barrier discharge plasma hydrophilic modification treatment can be 30 to 70 W, preferably 60 W. Studies have found that the water contact angle of the carbon fiber cloth treated by the dielectric barrier discharge plasma hydrophilic modification treatment at the preferred power is smaller and the hydrophilicity is better.
[0022] In step 1, the dielectric barrier discharge plasma hydrophilic modification treatment time can be 9 to 18 minutes, preferably 18 minutes. Studies have found that the water contact angle of the carbon fiber cloth treated with dielectric barrier discharge plasma hydrophilic modification under the preferred time is smaller and the hydrophilicity is better.
[0023] In step 1, the voltage of the dielectric barrier discharge plasma hydrophilic modification treatment may be 10 to 30 kV, such as 20 kV.
[0024] In step 1, the frequency of the dielectric barrier discharge plasma hydrophilic modification treatment may be 10 to 30 kHz, such as 20 kHz.
[0025] In step 1, the thickness of the dielectric layer treated by dielectric barrier discharge plasma hydrophilic modification can be 1 to 2 mm.
[0026] In step 1, the dielectric layer used in the dielectric barrier discharge plasma hydrophilic modification treatment may be quartz.
[0027] In step 1, the discharge spacing between the two electrodes used in the dielectric barrier discharge plasma hydrophilic modification treatment can be 3 to 6 mm, and can further be 3 to 4 mm.
[0028] In step 2, the molar ratio of cobalt to yttrium in the mixed solution is preferably 6: 1. Studies have found that when the total molar number of cobalt and yttrium in the mixed solution is constant, the cobalt-yttrium bimetallic oxygen / nitride electrocatalytic material has the best electrocatalytic performance when the molar ratio of cobalt to yttrium is 6: 1.
[0029] In step 2, the temperature of the hydrothermal reaction is preferably 250° C. Studies have found that the electrocatalytic performance of the cobalt-yttrium bimetallic oxygen / nitride electrocatalytic material is better at a preferred hydrothermal reaction temperature.
[0030] In step 2, the hydrothermal reaction time is preferably 10 hours. Studies have found that the electrocatalytic performance of the cobalt-yttrium bimetallic oxygen / nitride electrocatalytic material is better under the preferred hydrothermal reaction time.
[0031] [2] The Y2O3 / YN-Co3O4 cobalt yttrium bimetallic oxide / nitride electrocatalyst material prepared by the preparation method described in [1]. Furthermore, the Y2O3 / YN-Co3O4 cobalt yttrium bimetallic oxide / nitride in the Y2O3 / YN-Co3O4 cobalt yttrium bimetallic oxide / nitride electrocatalyst material has a polyhedral micro-nano particle structure.
[0032] [3] Application of the Y2O3 / YN-Co3O4 cobalt-yttrium bimetallic oxygen / nitride electrocatalyst material described in [2] in the electrolysis of water to produce hydrogen and oxygen.
[0033] In the current selection of catalytic substrates, carbon cloth is not the preferred substrate material due to its relatively low specific surface area and poor electrical conductivity. The present invention cleverly uses dielectric barrier discharge plasma to modify the surface of carbon cloth, create a large number of defects, improve its hydrophilicity and greatly enhance its binding force with the catalytic material. The plasma-modified carbon cloth not only loads a large amount of Y2O3 / YN-Co3O4 cobalt-yttrium bimetallic oxygen / nitride, but also significantly improves the catalytic performance, electrical conductivity and stability of the electrocatalyst. Its unique morphological characteristics are more conducive to improving the corrosion resistance of the catalyst. The prepared Y2O3 / YN-Co3O4 cobalt-yttrium bimetallic oxygen / nitride electrocatalyst further improves the electrocatalytic performance of the material.
[0034] Compared with the prior art, the present invention has the following beneficial effects:
[0035] The present invention proposes a dielectric barrier discharge plasma-assisted preparation of Y2O3 / YN-Co3O4 cobalt-yttrium bimetallic oxygen / nitride electrocatalyst. The prepared Y2O3 / YN-Co3O4 cobalt-yttrium bimetallic oxygen / nitride electrocatalyst is uniformly attached to carbon fiber. The catalyst loading rate without plasma assistance is low. The electrocatalytic material (catalyst) of the present invention has excellent electrocatalytic performance. Compared with traditional metal oxides, the catalyst has the characteristics of ultra-large active surface area, abundant active centers and rapid electron transfer, thereby ensuring that its performance under high current density and industrial-related conditions is better than other precious metal catalysts. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 The present invention is a schematic flow diagram of a method for preparing a cobalt-yttrium bimetallic oxygen / nitride electrocatalyst material, wherein: carbon fiber cloth (CC) 1, dielectric barrier discharge 2, pretreated carbon fiber cloth (PCC) 3, polytetrafluoroethylene high-pressure reactor 4, Y2O3 / YN-Co3O4 cobalt-yttrium bimetallic oxygen / nitride electrocatalyst material 5.
[0037] Figure 2 This is a photograph of the morphological characteristics of the carbon fiber surface after modification by dielectric barrier discharge plasma in Example 1.
[0038] Figure 3 This is a low-resolution scanning electron microscope photograph of the cobalt-yttrium bimetallic oxygen / nitride catalyst in Example 1.
[0039] Figure 4 This is a high-resolution scanning electron microscope photograph of the cobalt-yttrium bimetallic oxygen / nitride catalyst in Example 1.
[0040] Figure 5 This is a low-resolution scanning electron microscope photograph of the catalyst in Comparative Example 2.
[0041] Figure 6 This is a high-resolution scanning electron microscope photograph of the catalyst in Comparative Example 2.
[0042] Figure 7 This is the X-ray diffraction (XRD) pattern of the cobalt-yttrium bimetallic oxygen / nitride catalyst of Example 1.
[0043] Figure 8 This is a transmission electron microscope photograph of the cobalt-yttrium bimetallic oxygen / nitride catalyst of Example 1.
[0044] Fig. 9 This is the X-ray photoelectron spectroscopy (XPS) graph of the cobalt-yttrium bimetallic oxygen / nitride catalyst N1s of Example 1.
[0045] Fig.10 These are the hydrogen evolution polarization curves of the cobalt-yttrium bimetallic oxygen / nitride catalyst in Example 1, the Co3O4 / PCC prepared in Comparative Example 1, the Y2O3-Co3O4 / CC prepared in Comparative Example 2, the carbon fiber (PCC) treated with dielectric barrier discharge plasma in Comparative Example 3, and the Pt / C / PCC catalyst in Comparative Example 4.
[0046] Fig.11 These are the oxygen evolution polarization curves of the cobalt-yttrium bimetallic oxygen / nitride catalyst in Example 1, the Co3O4 / PCC prepared in Comparative Example 1, the Y2O3-Co3O4 / CC prepared in Comparative Example 2, the carbon fiber (PCC) treated with dielectric barrier discharge plasma in Comparative Example 3, and the RuO2 / PCC catalyst in Comparative Example 4.
[0047] Fig.12 This is a curve chart of the hydrogen evolution stability test of the cobalt-yttrium bimetallic oxygen / nitride in Example 1.
[0048] Fig.13 This is a curve chart of the oxygen evolution stability test of the cobalt-yttrium bimetallic oxygen / nitride in Example 1. DETAILED DESCRIPTION
[0049] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention.
[0050] Embodiment 1:
[0051] See also Figure 1 , a method for preparing a cobalt-yttrium bimetallic oxygen / nitride electrocatalytic material, comprising:
[0052] Step 1: The surface of the carbon fiber cloth is modified by a dielectric barrier discharge device to obtain a base PCC. The specific method is as follows: First, the carbon fiber cloth is soaked in 20mL of acetone and 20mL of 3M hydrochloric acid solution, and then ultrasonically cleaned for about 30 minutes, and then ultrasonically cleaned with 30mL of ethanol and 30mL of deionized water for 10 minutes to completely remove surface impurities. The cleaned carbon fiber is placed in a vacuum drying oven and dried at 50°C for 2h. The dried carbon fiber cloth is transferred to a dielectric barrier discharge device with a voltage of 20kV, a frequency of 20KHz, a quartz dielectric layer thickness of 2mm, a flat plate discharge gap of 4mm, and a plasma discharge treatment power of 60W and a plasma discharge time of 18min to obtain a hydrophilic base PCC.
[0053] Step 2: Weigh cobalt nitrate hexahydrate and yttrium nitrate hexahydrate according to the total molar number of cobalt and yttrium 2mmol and the molar ratio of cobalt to yttrium 6:1, and dissolve them in 20mL deionized water, and stir with a magnetic stirrer until the solution is completely transparent. Subsequently, 0.22g of ammonium fluoride and 0.48g of urea are added. The treated carbon fiber cloth PCC and the above-mentioned solution are transferred to a 50mL polytetrafluoroethylene high-pressure reactor, and the reactor is placed in a blast drying oven for hydrothermal reaction after sealing. The reaction temperature is controlled at 250°C and the reaction time is 10h. After the reaction is completed, the reaction system is cooled to room temperature, the sample is taken out and washed several times with deionized water and anhydrous ethanol respectively, and the residue in the solution is completely removed. Finally, the cleaned sample is dried in a blast drying oven at a temperature range of 50°C to finally obtain a cobalt-yttrium bimetallic oxygen / nitride catalyst, i.e., a Y2O3 / YN-Co3O4 cobalt-yttrium bimetallic oxygen / nitride electrocatalytic material.
[0054] This method uses a plasma-assisted hydrothermal method to in situ prepare a cobalt-yttrium bimetallic oxide / nitride catalyst on a carbon fiber cloth substrate. It has the advantages of simplicity, high efficiency, and low cost, and provides a new technical route for the preparation of cobalt-yttrium bimetallic oxide / nitride catalysts. The prepared catalyst has excellent electrocatalytic performance and stability.
[0055] Comparative Example 1:
[0056] The only difference from Example 1 is that yttrium nitrate hexahydrate is not added, that is, in step 2, cobalt nitrate hexahydrate is weighed according to the molar number of cobalt 2 mmol, and the rest is the same to obtain a Co3O4 / PCC catalyst.
[0057] Comparative Example 2:
[0058] The only difference from Example 1 is that the carbon limiting cloth has not been treated with plasma, and the rest are the same. The obtained catalyst was characterized by XPS and no N1s peak was found, that is, there was no nitride in the catalyst, and it was recorded as Y2O3-Co3O4 / CC catalyst.
[0059] Comparative Example 3:
[0060] Referring to step 1 of Example 1, a hydrophilic base PCC was obtained.
[0061] Comparative Example 4:
[0062] The noble metal electrocatalysts Pt / C / PCC and RuO2 / PCC were prepared by drop coating. 3.78 mg of RuO2 or Pt / C powder was dispersed into a solution containing 525 μL of ethanol, 187 μL of water, and 50 μL of 5% Nafion solution, and then the mixture was ultrasonically treated to form a uniform ink. Subsequently, the ink was dropped on the PCC surface of Comparative Example 3 and further dried to obtain RuO2 / PCC and Pt / C / PCC catalysts.
[0063] Through the examples and comparative examples, combined Figures 2 to 13 And the analysis of Table 1 and Table 2 is as follows:
[0064] Figure 2 The physical effect of the dielectric barrier discharge on the carbon fiber surface in Example 1 is shown, and a large number of defects of varying degrees are present on the carbon fiber surface, which increases its specific surface area, provides growth sites for metal sources, and improves the mass transfer efficiency of the material.
[0065] Figure 3 , Figure 4 The morphological characteristics of the cobalt-yttrium bimetallic oxygen / nitride catalyst of Example 1 are shown.
[0066] Figure 5 , Figure 6 The morphological characteristics of the catalyst in Comparative Example 2 are shown. Figure 3 , Figure 4 The morphology comparison of the cobalt-yttrium bimetallic oxygen / nitride catalyst in Example 1 shows that the cobalt-yttrium bimetallic active component has a higher loading density on the plasma-modified carbon fiber cloth.
[0067] Figure 7 It shows that the cobalt-yttrium bimetallic oxygen / nitride catalyst of Example 1 contains Y2O3, YN, and Co3O4 crystal phases. Figure 8 It shows that the cobalt-yttrium bimetallic oxygen / nitride catalyst of Example 1 contains YN and Co3O4 phases. Fig. 9 The cobalt-yttrium bimetallic oxygen / nitride catalyst of Example 1 contains N bonded to the metal, combined with Figure 7 , Figure 8 The characterization shows that its source should be YN. Figures 7 to 9 The characterizations complement each other, indicating that Example 1 indeed obtained the Y2O3 / YN-Co3O4 cobalt-yttrium bimetallic oxygen / nitride electrocatalytic material.
[0068] Fig.10Table 1 shows the test of hydrogen evolution performance of different catalysts using a three-electrode system in a 1.0 M potassium hydroxide solution, including the cobalt-yttrium bimetallic oxygen / nitride catalyst (301 mV) in Example 1, the Co3O4 / PCC prepared in Comparative Example 1 (395 mV), the Y2O3-Co3O4 / CC prepared in Comparative Example 2 (424 mV), the PCC obtained by treating carbon fiber with dielectric barrier discharge plasma in Comparative Example 3, and the Pt / C / PCC catalyst in Comparative Example 4 at a current density of 1000 mA cm -2 The overpotential value of the hydrogen evolution reaction.
[0069] Fig.11 Table 2 shows the oxygen evolution performance of different catalysts tested using a three-electrode system in a 1.0 M potassium hydroxide solution, including the cobalt-yttrium bimetallic oxygen / nitride catalyst (360 mV) in Example 1, the Y2O3-Co3O4 / CC (440 mV) prepared in Comparative Example 2, the Co3O4 / PCC (480 mV) prepared in Comparative Example 1, the PCC obtained by treating carbon fiber with dielectric barrier discharge plasma in Comparative Example 3, and the RuO2 / PCC (430 mV) catalyst in Comparative Example 4 at a current density of 500 mA cm -2 The overpotential value of the oxygen evolution reaction.
[0070] Fig.12 The figure shows the hydrogen evolution stability test of Example 1 at different current densities in 1.0 M potassium hydroxide solution.
[0071] Fig.13 The oxygen evolution stability test of Example 1 at different current densities in 1.0 M potassium hydroxide solution is shown.
[0072] Table 1 shows the performance of the cobalt-yttrium bimetallic oxygen / nitride catalyst in Example 1, the Co3O4 / PCC prepared in Comparative Example 1, the Y2O3-Co3O4 / CC catalyst prepared in Comparative Example 2, the carbon fiber (PCC) treated with dielectric barrier discharge plasma in Comparative Example 3, and the Pt / C / PCC catalyst in Comparative Example 4 at a current density of 1000 mA cm -2 The overpotential value of the hydrogen evolution reaction.
[0073] Table 1
[0074]
[0075] Table 2 shows the catalyst performance of the cobalt-yttrium bimetallic oxygen / nitride catalyst in Example 1, the Co3O4 / PCC prepared in Comparative Example 1, the Y2O3-Co3O4 / CC catalyst prepared in Comparative Example 2, the carbon fiber (PCC) treated with dielectric barrier discharge plasma in Comparative Example 3, and the RuO2 / PCC catalyst in Comparative Example 4 at a current density of 500 mA cm -2The overpotential value of the oxygen evolution reaction.
[0076] Table 2
[0077]
[0078] In addition, it should be understood that after reading the above description of the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application.
Claims
1. A method for preparing a cobalt-yttrium bimetallic oxygen / nitride electrocatalytic material, characterized in that: include: Step 1: using dielectric barrier discharge plasma to hydrophilically modify the carbon fiber cloth; Step 2: adding the carbon fiber cloth treated in step 1 to a mixed solution containing cobalt (II) nitrate, yttrium (III) nitrate, ammonium fluoride and urea, and placing them together in a high-pressure reactor for hydrothermal reaction to obtain a Y2O3 / YN-Co3O4 cobalt-yttrium bimetallic oxygen / nitride electrocatalytic material; The molar ratio of cobalt to yttrium in the mixed solution is 5 to 7:1; In the mixed solution, the mass ratio of the total molar number of cobalt and yttrium to the mass ratio of ammonium fluoride and urea is 2mmol:(0.2-0.3)g:(0.4-0.5)g; The temperature of the hydrothermal reaction is 230-260°C; The hydrothermal reaction time is 8 to 11 hours.
2. The preparation method according to claim 1, characterized in that: In step one: The power of dielectric barrier discharge plasma hydrophilic modification treatment is 30-70W; The time of the dielectric barrier discharge plasma hydrophilic modification treatment is 9 to 18 minutes.
3. The preparation method according to claim 2, characterized in that: In step one: The power of the dielectric barrier discharge plasma hydrophilic modification treatment is 60W; The time of dielectric barrier discharge plasma hydrophilic modification treatment is 18 minutes.
4. The preparation method according to claim 1, characterized in that: In step one: The voltage of the dielectric barrier discharge plasma hydrophilic modification treatment is 10 to 30 kV; The frequency of the dielectric barrier discharge plasma hydrophilic modification treatment is 10 to 30 kHz; The thickness of the dielectric layer treated by dielectric barrier discharge plasma hydrophilic modification is 1 to 2 mm; The dielectric layer used in the hydrophilic modification treatment of dielectric barrier discharge plasma is quartz; The discharge distance between the two electrodes used in the dielectric barrier discharge plasma hydrophilic modification treatment is 3 to 6 mm.
5. The preparation method according to claim 1, characterized in that: In step 2, the molar ratio of cobalt to yttrium in the mixed solution is 6:
1.
6. The preparation method according to claim 1, characterized in that: In step 2, the temperature of the hydrothermal reaction is 250° C., and the time of the hydrothermal reaction is 10 hours.
7. The Y2O3 / YN-Co3O4 cobalt-yttrium bimetallic oxygen / nitride electrocatalytic material prepared according to the preparation method according to any one of claims 1 to 6.
8. The Y2O3 / YN-Co3O4 cobalt-yttrium bimetallic oxygen / nitride electrocatalytic material according to claim 7, characterized in that: The Y2O3 / YN-Co3O4 cobalt yttrium bimetallic oxygen / nitride in the Y2O3 / YN-Co3O4 cobalt yttrium bimetallic oxygen / nitride electrocatalytic material has a polyhedral micro-nano particle structure.
9. Use of the Y2O3 / YN-Co3O4 cobalt-yttrium bimetallic oxygen / nitride electrocatalytic material according to claim 7 or 8 in the electrolysis of water to produce hydrogen and oxygen.